2006
DOI: 10.1097/01.bsd.0000211234.68469.92
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis of the Atlantoaxial Joint

Abstract: Bacterial epidural abscess formation of cervical spine was rarely seen and all these cases were associated with osteomyelitis of the odontoid process. To the author's knowledge, only 1 case of septic arthritis of the C1-C2 lateral facet joint has been reported in the English literature. A 76-year-old woman presented with progressive neck pain and stiffness in the left side of her neck with fever. Coronal computed tomography clearly demonstrated destructive change of the atlantoaxial joint. Contrast magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the case of early diagnosis of infection of the upper cervical spine region, conservative treatment with antibiotics and immobilization is likely to be sufficient 15,16 as was shown in this case. In the current case, CT scanning was done immediately because of severe neck pain and the clinical suspicion of inflammatory disease.…”
Section: Discussionmentioning
confidence: 79%
“…In the case of early diagnosis of infection of the upper cervical spine region, conservative treatment with antibiotics and immobilization is likely to be sufficient 15,16 as was shown in this case. In the current case, CT scanning was done immediately because of severe neck pain and the clinical suspicion of inflammatory disease.…”
Section: Discussionmentioning
confidence: 79%
“…Elias 8 reported a single case of subaxial epidural abscess after a trigger point injection. Halla and associates 10 and Sasaki et al 19 have both reported septic arthritis of the atlantoaxial joint, but these cases did not involve prior injection therapy. Yazawa and colleagues 24 described a case of cervical epidural abscess and osteomyelitis of C-1 and C-2 after acupuncture treatment for chronic neck pain.…”
Section: Discussionmentioning
confidence: 98%
“…Early infection of the atlanto-axial junction is difficult to diagnose, as symptoms are usually vague and variable, and radiographs usually show overlapping shadow of the occiput, maxillary sinus and dental artefacts. 5 When the diagnosis is early, antibiotic treatment alone should suffice 1,6 ; otherwise, surgical drainage is needed. Prompt diagnosis requires a high degree of clinical suspicion, with timely use of modern imaging modalities.…”
Section: Discussionmentioning
confidence: 99%